Estratégias de comunicação da marca Boca Rosa Beauty: estudo de caso durante o cancelamento virtual - Farias, Yamille Miranda (Brasil, 2023)
This study aims to analyze the communication strategies and how the Boca Rosa Beauty brand reversed the cancellation of founder Bianca Andrade. The specific objective of this analysis is to identify Public Relations activities adopted by the brand in crisis situations, through communication strategies. In addition to the elaboration of a practical guide with the main communication strategies that can be applied in case of cancellation in order to help other companies and provide practical guidance for students and communication professionals. Theoretical fundamentals of communication and marketing are presented, in addition to concepts that help in the analysis of the case study. The methodological procedures were bibliographic research and documentary research, with a qualitative approach. The results show how a brand that eventually faces the cancellation crisis can position itself so as not to harm its image and profitability, and still obtain an increase in sales. In addition to preparing a practical guide to help other companies adopt communication strategies that can solve the virtual cancellation.